The effectiveness of a motivation camp programme among second and third year students of biomedical science - Nurul Farhana Jufri,; Nur Zakiah M. Saat,; Syarif Husin Lubis,; Ismarulyusda Ishak,; Siti Fathiah Masre, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Motivation camp is one of the learning interventions to assist underperform students in improving their academic performances in term of GPA (Grade Point Average). An intervention study was carried out to know the effectiveness of a motivation camp in improving the academic performances among the biomedical science students at the Universiti Kebangsaan Malaysia, Kuala Lumpur. Total of 44 respondents were involved in this study from year 2 and year 3 and had been categorized into control and intervention groups (n = 22 per group). The intervention group was given motivational talks followed by a group discussion and self-reflection. The students in the intervention group were also assigned with academicians to facilitate and guide them throughout the motivational camp. The students were interested in motivational talks activity the most. The average GPA showed a significant improvement after the motivation camp with 3.01 ± 0.30 (p < 0.05) for the intervention group. Yet, control group also displayed a significant increment in the average GPA, 3.24 ± 0.06 (p < 0.05). In conclusion, motivation camp is one of the many learning intervention tools that strategize to help students in improving their academic performances but it should be complemented with other intervention methods.